2022
DOI: 10.3390/ijerph19042300
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Willingness to the COVID-19 Vaccine Booster Shots among Urban Employees: Evidence from a Megacity H in Eastern China

Abstract: Many studies have shown that urban workers may have a higher acceptance rate of coronavirus disease (COVID-19) vaccine uptake compared to their rural counterparts. As Omicron spreads globally, the COVID-19 booster vaccination has been acknowledged as the primary strategy against this variant. In this study, we identify factors related to the willingness of workers in megacities to take the vaccine booster shots and their main reasons accounting for their booster willingness. This research survey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
8
22
1
Order By: Relevance
“…Our findings differ from studies by Qin et al and Folcarelli et al The 21–30 age group ( 31 ) and the older participants ( 36 ) demonstrated the lowest hesitancy, respectively. Consistent with evidence from existing literature ( 29 ), females were reluctant to receive the booster dose. Social media reports demonstrate disturbances in the menstrual cycle.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our findings differ from studies by Qin et al and Folcarelli et al The 21–30 age group ( 31 ) and the older participants ( 36 ) demonstrated the lowest hesitancy, respectively. Consistent with evidence from existing literature ( 29 ), females were reluctant to receive the booster dose. Social media reports demonstrate disturbances in the menstrual cycle.…”
Section: Discussionsupporting
confidence: 85%
“…Other 36) demonstrated the lowest hesitancy, respectively. Consistent with evidence from existing literature (29), females were reluctant to receive the booster dose. Social media reports demonstrate disturbances in the menstrual cycle.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found a positive association between confidence in COVID-19 vaccination and second booster acceptance. Previous studies confirm this finding since confidence in the safety and effectiveness of COVID-19 vaccines and trust in pharmaceutical companies improved first COVID-19 booster acceptance rate and increased the number of vaccinated people [ 15 , 16 , 20 , 21 , 36 , 37 ]. Moreover, vaccine efficacy and effectiveness is associated with COVID-19 vaccine acceptance and uptake [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 66%
“…These findings are consistent with third dose vaccination intentions in the United Kingdom (10), though other research suggests socioeconomic status has little impact. (11,30) Encouragingly, other populations thought to be at risk for undervaccination (e.g. newcomers, first language not English or French, Indigenous identity) in Canada (31), reported third dose vaccination intentions that were not significantly different from the general population or more positive.…”
Section: Discussionmentioning
confidence: 99%